Gums and stabilisers for the food industry 11 : [the proceedings of the Eleventh Gums and Stabilisers for the Food Industry Conference-Crossing Boundaries held on 2-6 July 2001 at The North East Wales Institute, Wrexham, UK] - Williams, Peter A.; Phillips, Glyn O. (Royal Society of Chemistry, 2002)
The breadth and depth of knowledge of gums and stabilisers has increased tremendously over the last two decades, with researchers in industry and academia collaborating to accelerate the growth. Gums and Stabilisers for the Food Industry 11 presents the latest research in the field of hydrocolloids used in food. Bringing together contributions from international experts, the first section of the book investigates the advances in structure determination and characterisation of hydrocolloids, including the use of capillary electrophoresis. Later sections deal with rheological aspects of hydrocolloids in solutions and gels; the application of hydrocolloids in real food systems; and the interfacial behaviour and gelation of proteins. A discussion of the influence of hydrocolloids on human health is also included. Researchers and other professionals in industry and academia, particularly those involved directly with food science, will welcome this title as a source of the very latest information.
Keywords: Gums and resins -- Congresses.; Stabilizing agents -- Congresses.; Food additives -- Congresses.; elektronické knihy; electronic books